2002
DOI: 10.1159/000048211
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Exercise Increases Both Inducible and Endothelial Nitric Oxide Synthase Gene Expression in Endothelial Cells of Rat Aorta

Abstract: Chronic exercise upregulates endothelial nitric oxide synthase (eNOS) gene expression. Whether the expression of inducible nitric oxide synthase (iNOS) is affected by exercise is unknown. We therefore investigated the effects of chronic exercise on iNOS and eNOS expression in isolated rat aortic endothelial and smooth muscle cells separately. Five-week-old male Wistar rats were randomly divided into control and exercise groups. After 10 weeks of running training, animals were sacrificed under ether anesthesia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Daily exercise has been found to promote eNOS expression and alleviate negative changes in hypertensive rats (Moraes-Teixeira et al 2010). Physical activity also promotes NO activity in ovariectomized rats (Lee et al 2012) and eNOS and iNOS mRNA expression in aorta (Yang et al 2002). This is in line with the results of the current study as in both running experimental groups the expression of eNOS and nNOS in similar to control group while it is lower in supplemented notrunning groups.…”
Section: Discussionsupporting
confidence: 90%
“…Daily exercise has been found to promote eNOS expression and alleviate negative changes in hypertensive rats (Moraes-Teixeira et al 2010). Physical activity also promotes NO activity in ovariectomized rats (Lee et al 2012) and eNOS and iNOS mRNA expression in aorta (Yang et al 2002). This is in line with the results of the current study as in both running experimental groups the expression of eNOS and nNOS in similar to control group while it is lower in supplemented notrunning groups.…”
Section: Discussionsupporting
confidence: 90%
“…In L-NNA-treated rats that were stimulated, depressed basal NO production was established by the significant rise in mean arterial pressure, which equalled that seen with much higher oral doses [30]. On the assumption that in our experiments NO blockade was effective, the effects of chronic stimulation could be due to reversal of this, possibly by activity-induced up-regulation of NOS gene expression [31]or increased eNOS phosphorylation [32]. …”
Section: Discussionmentioning
confidence: 90%
“…Examination of the time-course of training-induced increases in aortic EDD revealed no change following a single exercise bout or after training durations of less than four weeks, but aortic EDD was increased following training programs of 4 weeks and 10 weeks (7). Subsequent studies using 8-10 weeks of training in rats (5,6,61) confirmed these results (see Table 1). Also, 16-19 weeks of training in pigs (45) produce changes in aortic endothelial gene expression consistent with enhanced EDD following long term training.…”
Section: Conduit Arteriesmentioning
confidence: 81%